Eosinophils from Physiology to Disease: A Comprehensive Review. (28th January 2018) - Ramirez, Giuseppe A.; Yacoub, Mona-Rita; Ripa, Marco; Mannina, Daniele; Cariddi, Adriana; Saporiti, Nicoletta; Ciceri, Fabio; Castagna, Antonella; Colombo, Giselda; Dagna, Lorenzo
Abstract : Despite being the second least represented granulocyte subpopulation in the circulating blood, eosinophils are receiving a growing interest from the scientific community, due to their complex pathophysiological role in a broad range of local and systemic inflammatory diseases as well as in cancer and thrombosis. Eosinophils are crucial for the control of parasitic infections, but increasing evidence suggests that they are also involved in vital defensive tasks against bacterial and viral pathogens including HIV. On the other side of the coin, eosinophil potential to provide a strong defensive response against invading microbes through the release of a large array of compounds can prove toxic to the host tissues and dysregulate haemostasis. Increasing knowledge of eosinophil biological behaviour is leading to major changes in established paradigms for the classification and diagnosis of several allergic and autoimmune diseases and has paved the way to a "golden age" of eosinophil-targeted agents. In this review, we provide a comprehensive update on the pathophysiological role of eosinophils in host defence, inflammation, and cancer and discuss potential clinical implications in light of recent therapeutic advances.